Assessing the health impact of transnational corporations: a case study on McDonald's Australia. Issue 1 (December 2017) - Anaf, Julia; Baum, Frances; Fisher, Matt; Harris, Elizabeth; Friel, Sharon
Abstract Background The practices of transnational corporations affect population health through production methods, shaping social determinants of health, or influencing the regulatory structures governing their activities. There has been limited research on community exposures to TNC policies and practices. Our pilot research used McDonald's Australia to test methods for assessing the health impacts of one TNC within Australia. Methods We adapted existing Health Impact Assessment methods to assess McDonald's activities. Data identifying potential impacts were sourced through document analysis, including McDonald's corporate literature; media analysis and semi-structured interviews. We commissioned a spatial and socioeconomic analysis of McDonald's restaurants in Australia through Geographic Information System technology. The data was mapped against a corporate health impact assessment framework which included McDonald's Australia's political and business practices; products and marketing; workforce, social, environmental and economic conditions; and consumers' health related behaviours. Results We identified both positive and detrimental aspects of McDonald's Australian operations across the scope of the CHIA framework. We found that McDonald's outlets were slightly more likely to be located in areas of lower socioeconomic status. McDonald's workplace conditions were found to be more favourable than those in many other countries which reflects compliance with Australian employment regulations. The breadth of findings revealed the need for governments to strengthen regulatory mechanisms that are conducive to health; the opportunity for McDonald's to augment their corporate social responsibility initiatives and bolster reputational endorsement; and civil society actors to inform their advocacy towards health and equity outcomes from TNC operations. Conclusion Our study indicates that undertaking a corporate health impact assessment is possible, with the different methods revealing sufficient information to realise that strong regulatory frameworks are need to help to avoid or to mediate negative health impacts.